(untitled) (Journal of the College of Education for Women, 2023)
Sultan Said bin Sultan bin Ahmed bin Said Al-Busaidi (1223-1273 AH / 1806-1856 AD) was able to rule Oman and Zanzibar in a unified Arab-African state during his reign. However, it was separated for several reasons. Thus, the study aims to clarify the efforts made by Sultan Said for annexing Zanzibar to Oman, establishing the Arab-African Sultanate, and shedding light on the role played by Britain in dividing the Arab-African Sultanate and separating Zanzibar from the Omani rule in (1275 AH-1861 AD). The study has adopted the historical descriptive analytical approach. The study has reached several conclusions, such as: The economic motivators are the most important factors that push Sultan Said to move his capital from Muscat to Zanzibar in 1832 AD, and settle there until 1840 AD. At that time, Sultan Said bin Sultan laid the necessary foundations and pillars for the advancement of the unified Arab-African Sultanate. Further, he signed several agreements with some European countries to revive trade in the Sultanate. The study has finally recommended to: pursue the interest in the history of Oman and Zanzibar, focus on Britain’s relationship with Zanzibar during the reign of Sultan Saeed, and on the impact of the political differences among the sons of Sultan Saeed after his death, Majid bin Saeed and Thuwaini bin Saeed on dividing the unified Arab-African Sultanate. It has also recommended to shed more light on the industrial activity in Zanzibar during Sultan Said bin Sultan bin Ahmed bin Said Al-Busaidi’s rule.